Cumulative Impact of Federal and State Policy on Minimum Selling Price of Sustainable Aviation Fuel - Brandt, Kristin L.; Martinez-Valencia, Lina; Wolcott, Michael P. (Frontiers in Energy Research, 2022)
With jet fuel consumption projected to more than double by 2050, dramatic expansion of sustainable aviation fuel (SAF) use will be essential to meeting the aviation industry goal of achieving carbon neutrality in the same time frame. However, to date, the SAF price has, in part, been responsible for the lack of widespread adoption signaling the need for strong and stable policy. Multiple pathways have been developed and received ASTM approval to convert a variety of feedstocks into SAF, each with strengths and weaknesses that vary with conversion technology, feedstock, and production location. To assist researchers and governments in understanding the role of policy on fuel pricing, a set of harmonized, techno-economic analyses (TEAs) were developed to assess three ASTM-qualified production pathways: hydroprocessed esters and fatty acids (HEFAs), alcohol to jet (ATJ), and Fischer–Tropsch (FT), with multiple feedstock options. These decision support tools were used to assess the minimum selling price (MSP) for fuel distillates. Both mature (nth) plants and first of a kind (pioneer plants) were assessed using TEAs. Existing and proposed U.S. incentives, at both the federal and state levels, were integrated into the tools to determine the impact on the MSP. Considering the existing federal policies, analysis indicated that HEFAs could achieve a SAF price that would be competitive to conventional fuels when using waste lipid feedstocks, making this the most viable near-term option. However, this feedstock for HEFAs is limited and unlikely to support the production of large quantities of SAF. After stacking federal and state programs, SAF produced using FT with municipal solid waste (MSW) has the lowest MSP, although FT forest residuals, FT agricultural residues, ATJ corn ethanol, and HEFAs using second crop oilseeds all approach the historical range of traditional jet fuel prices for nth plants. Pioneer plants are viable for only ATJ corn ethanol; however, FT-MSW is approaching price parity.